Pemanfaatan Palm Oil Fuel Ash (POFA) Sebagai Pengganti Sebagian Agregat Halus dalam Campuran Beton - Nasution, Ari Endra; Wijaya, Sucitra; Christalline, Silvia; Renjani, Muhammad Sodri (Universitas Batanghari Jambi, 2025)
This study investigates using Palm Oil Fuel Ash (POFA) as a partial substitute for some of fine aggregate (sand) in concrete mixtures. The goal is to determine the optimal percentage of POFA by testing several variations of its use as a substitute for fine aggregate. The study employed an experimental methodology involving the preparation of 15 cm x 15 cm x 15 cm cubic test specimens in accordance with SNI 03-2834-2000 (Procedures for Preparing Normal Concrete Mix Designs). The POFA percentages were 0% (control specimen), 5%, 6%, 7%, 8%, 9%, 10%, and 20%. Test results showed that the compressive strength of concrete produced using 0% POFA (normal concrete) was 228.6 kg/cm². The compressive strengths of concrete produced using 5%, 6%, 7%, 8%, 9%, and 10% POFA were 134.9, 156.9, 159.7, 198.3, 198.3, and 151.5, 159,7 kg/cm², respectively. The test results indicate that adding POFA to the concrete decreased its compressive strength relative to control specimen. However, substituting fine aggregate with POFA at 8% and 9% resulted in higher compressive strength than the other variations. The results also indicated the potential for an increase in concrete compressive strength between 10% and 20%.